Fit for war : sustenance and order in the mid-eighteenth-century Catawba Nation - Fitts, Mary Elizabeth (Ripley P. Bullen series., 2017)
This study reveals how Catawba settlement aggregation, refugee incorporation, and political coalescence affected the scale of interaction networks and communities in the lower Catawba River valley. It also defines the crucial strategies employed in response to food security crises, daily life, and the roles of both men and women. This study highlights the double-edged nature of strategies available to American Indian groups seeking to maintain political autonomy in early colonial period contexts.